DEVELOPMENT OF SUSTAINABLE HEALTHCARE MODEL FOR THE HOSPITALS IN NORTHERN INDIA - Hima Gupta; Shweta Garg; Utkarsh Gupta (Indonesian Journal of Health Administration, 2023)
Background: Healthcare organizations incorporate products and services at economical prices to deliver healthcare services of good quality. All the operations performed in the organizations aimed to achieve a higher level of environmental sustainability governed by the Sustainable Developmental Goals of 2030. Aims: This study aims to develop a sustainable healthcare model using Analytical Hierarchy Process (AHP). Methods: First and foremost, the authors have identified the factors associated with the sustainable healthcare system through a literature review. Based on these factors, a questionnaire was developed and administered to 25 healthcare organizations from December 2020 to March 2021. An Analytical Hierarchy Process is utilized to rank the factors, and a conceptual model is developed. The Felix Hospitals substantiate this model. The authors have also applied sensitivity analysis to validate the results achieved via AHP. Results: The AHP model demonstrates the focus is on the environment first, followed by the economic and social dimensions sustainably. The validated model was also substantiated by the hospital (Felix) results and sensitivity analysis. Conclusion: It can be concluded that hospital sustainability highly depends on the environment in the first stage and economic and social sustainability in the second and third stages. The same result was achieved through AHP.  Keywords: analytical hierarchy process, hospital, sustainable healthcare.